Developing Advanced Cognitive Apprenticeships Model for Making the Students Creative and Self-Regulated Learners - khan, Yousaf; sultana, Naveed (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study was to develop a model of teaching and instruction that make the science students critical thinker, decision maker and self-regulated life-long and continuous learner as well as user of their cognitive and meta cognitive abilities.The main objective of the study was to apply advanced model of Cognitive Apprenticeships as an integrated model for teaching science subjects with application of learning theories at secondary level.The sample of the study was taken from all the students of class IX in both government and private schools of district swat for the target population of students of class IX in the session 2014 – 2015.The nature of the study was quasi-experimental. The pre-test post-test non-equivalent experimented group design was used and the data were collected after 16 weeks of teaching by the trained science teachers to plan their lesson according to the training manual designed by the researchers for the Ph.D. Thesis on Cognitive Apprenticeships model.The collected data were analyzed and Cohen’s d and t-test were used for testing the hypothesis and to find the effect size produced by the applied Cognitive Apprenticeships model.The findings of the study were concluded that the application of advanced Cognitive Apprenticeships as a new applied model for teaching science at secondary school level has produced significantly high effects on students’ achievement at Secondary School Level.Hence, it was recommended on the basis of findings and conclusion that the science teachers must be trained in Advanced Cognitive Apprenticeships during their pre-service and in-service training programs for secondary classes to nourish the students’ creativity for combating new challenges in science and technology through their science education with self-regulated and life-long learning qualities.